A comparison of growth rate of late Holocene stalagmites with atmospheric precipitation and temperature, and its implications for paleoclimatology. (1st May 2018) - Railsback, L. Bruce
Abstract: Growth rate of stalagmites can vary with many factors of physical environment, ecology, and karst hydrogeology, to the extent that growth rates calculated from a carefully selected set of data from 80 stalagmites from around the world vary by a factor of 400 from smallest to largest. Growth rates of those 80 stalagmites nonetheless collectively show correlations to atmospheric precipitation and temperature that are non-trivial ( r 2  = 0.12 and 0.20, respectively) and unlikely to have arisen randomly ( p  = 0.002 and 0.00002). Those global relationships are also supported by previously published studies of individual drip sites. The general trend of growth rates is not a monotonic increase with precipitation; instead, it reaches a maximum at annual precipitation rates between 700 and 2300 mm/year, which both counters many model predictions that growth rates should increase monotonically with drip rate and complicates use of growth rate as a proxy for past precipitation. The general trend of growth rates among the 80 stalagmites is a monotonic increase with temperature. However, the low values of r 2 in both of these general trends indicate that growth rate can be at best a qualitative rather than quantitative proxy of past conditions. Growth rate shows no statistically significant relationship to effective precipitation, seemingly because of the confounding effect of temperature. Growth rates of aragonite-bearing stalagmites are commonly greater than rates in stalagmites in which calcite is the only carbonate mineral, suggesting both the need for careful identification of mineralogy and the special applicability of aragonitic stalagmites in high-resolution studies. Aragonite has exceptionally great frequency in settings with low effective atmospheric precipitation, supporting previous linkages of that mineral to warm dry environments. Closely-spaced sampling used in recent paleoclimatological studies suggests that unexploited long-term low-resolution records of past climate may exist in surprisingly small slow-growing stalagmites from exceptionally cold and/or dry regions. Highlights: Growth rates vary greatly in set from 80 stalagmites, with highest ∼400 times lowest. General trend of growth rate of stalagmites is increase with increasing temperature. Growth rate increases with precipitation (P) at low P, decreases with P at high P. Growth rate is generally greater in aragonitic stalagmites.